Fragmenta Carabologica - 8. Revision der Untergattung Chaetomelas Thomson der Gattung Carabus L. (Col., Carabidae). - Mandl, Karl Ferdinand jun. (Contributions to Entomology = Beiträge zur Entomologie, 1987)
In the present revision all forms of the subgenus Chaetomelas Thomson of the genus Carabus L. are described and discussed. The taxa praestigiator Moeawitz, morawitzi Ganglbauer and piochardi Géhin are confirmed as bonae species and the taxon montesamanus Mandl will be reestablished as species. In the youngest time it have been without weighty arguments degraded to a subspecies, at first to praestigiator and four mothes later to morawitzi! Also the species bytinskii has been degraded to subspecies of praestigiator but in this revision will be demonstrated that bytinskii is a hybrid form identical with labruleriei Géhin. This taxon together with judaicus Géhin, till now subspecies of praestigiator, turned out as hybrid forms. The Autor has designed a specimen of piochardi in the collection of the Museum National d’Histoire Naturelle in Paris as Lectotypus. Nomenclatural Acts piochardi (Géhin, 1883) (Carabus (Chaetomelas)), Lectotype hitherto Carabus piochardi